2015
DOI: 10.1080/17439760.2015.1117131
|View full text |Cite
|
Sign up to set email alerts
|

Positive psychology in context: Effects of expressing gratitude in ongoing relationships depend on perceptions of enactor responsiveness

Abstract: Recent correlational evidence implicates gratitude in personal and relational growth, for both members of ongoing relationships. From these observations, it would be tempting to prescribe interpersonal gratitude exercises to improve relationships. In this experiment, couples were randomly assigned to express gratitude over a month, or to a relationally-active control condition. Results showed modest effects of condition on personal and relational well-being. However, those whose partners were perceived as bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 66 publications
3
93
0
3
Order By: Relevance
“…The current finding revealed that the implementation of intentional activities in couples' daily lives produced immediate changes from the pretest to the post‐test for some positive indicators (i.e., positive emotion, mutuality communication pattern, quality of interaction, and dyadic adjustment). The improvement in positive emotion was consistent with Coulter and Malouff's () 4‐week single‐component intervention and with Algoe and Zhaoyang's () 28‐day single‐component gratitude intervention. In the current study, couples in the intervention group showed improvements in dyadic variables (i.e., quality of interaction and dyadic adjustment) and in mutuality communication patterns over the course of the intervention compared with those in the control condition.…”
Section: Discussionsupporting
confidence: 80%
“…The current finding revealed that the implementation of intentional activities in couples' daily lives produced immediate changes from the pretest to the post‐test for some positive indicators (i.e., positive emotion, mutuality communication pattern, quality of interaction, and dyadic adjustment). The improvement in positive emotion was consistent with Coulter and Malouff's () 4‐week single‐component intervention and with Algoe and Zhaoyang's () 28‐day single‐component gratitude intervention. In the current study, couples in the intervention group showed improvements in dyadic variables (i.e., quality of interaction and dyadic adjustment) and in mutuality communication patterns over the course of the intervention compared with those in the control condition.…”
Section: Discussionsupporting
confidence: 80%
“…People who thank are more likely to feel grateful, and grateful people are more likely to reciprocate, are more prosocial (or concerned about others), and are better relationship partners (Algoe, Fredrickson, & Gable, 2013;Algoe, Gable, & Maisel, 2010;Algoe, Haidt, & Gable, 2008;Algoe, Kurtz, & Hilaire, 2016;Algoe & Haidt, 2009;Algoe & Zhaoyang, 2016;Bartlett, Condon, Cruz, Baumann, & Desteno, 2012;Bartlett & DeSteno, 2006;DeSteno, Bartlett, Baumann, Williams, & Dickens, 2010;Lambert et al, 2010;Lambert & Fincham, 2011;Williams & Bartlett, 2015). Similarly, people who apologize are often seen as more trustworthy and, like thankers, better relationship partners (Darby & Schlenker, 1982;Hannon, Rusbult, Finkel, & Kamashiro, 2010;Ho, 2012;Hodgins & Liebeskind, 2003;Kim et al, 2004Kim et al, , 2006Maio et al, 2008;McCullough et al, 1997;Weiner et al, 1991).…”
Section: Evidence Supporting the Tradeoffmentioning
confidence: 99%
“…RET builds on several streams of previous research, including empirical work on these communications in both psychology and economics (e.g., Abeler et al, 2010;Algoe & Zhaoyang, 2016;Darby & Schlenker, 1982;Deutsch & Lamberti, 1986;Grant & Gino, 2010;Ho, 2012;Ho & Liu, 2011;Hodgins & Liebeskind, 2003;Kim et al, 2004Kim et al, , 2006McGovern et al, 1975;Schlenker & Darby, 1981;Weiner, Graham, Peter, & Zmuidinas, 1991;Williams & Bartlett, 2015); empirical and theoretical work on person perception, self-presentation, and personal relationships in social psychology (e.g., Baumeister, 1982;P. Brown & Levinson, 1987;Fiske, Cuddy, Glick, & Xu, 2002;Fiske, Xu, Cuddy, & Glick, 1999;Goffman, 1959Goffman, , 1967Leary & Allen, 2011;Schlenker & Weigold, 1992); theoretical work on signaling from evolutionary biology (e.g., Grafen, 1990;Maynard-Smith & Harper, 2003;Zahavi, 1975;Zahavi & Zahavi, 1997); and empirical and theoretical work on language and communication in cognitive psychology (e.g., Goodman & Stuhlmüller, 2013;Grice, 1975;Pinker, 2011;Pinker, Nowak, & Lee, 2008;van Rooij, 2003;Yoon, Tessler, Goodman, & Frank, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being an individual level process, gratitude is embedded in a dynamic system (see Algoe & Zhaoyang, 2016). Displays of gratefulness, for example, may be transmitted from one dating partner to the other (Gordon, Impett, Kogan, Oveis, & Keltner, 2012), and gratitude for a partner's investment in the relationship can motivate an individual's commitment (Joel, Gordon, Impett, MacDonald, & Keltner, 2013).…”
Section: Individual Relationship Enhancementmentioning
confidence: 99%